CONSUMER PREFERENCES OF BIODEGRADABLE TOTE BAG PRODUCTS FROM SEAWEED CARRAGEENAN (Eucheuma cottoni) - Ine Maulina; Abiomi Ciptoning Bentali; Asep Agus Handaka Suryana (AQUASAINS, 2023)
Biodegradable tote bag is a processed carrageenan product from seaweed (Eucheuma cottoni) which is processed into fashion products. Consumer preferences are used to see consumer choices in determining the most preferred attributes of biodegradable tote bag products. This study aimed to see consumer preferences for biodegradable tote bag products. This research was conducted in Cibinong District, Bogor Regency as a general segmentation and Jatinangor District, Sumedang Regency as a special segmentation. The research method used was quantitative descriptive with analysis using frequency distribution and the Mann-Whitney U Test. The sampling technique was purposive sampling. The results showed that, out of the 6 attri-butes, there were 2 attributes that had a real difference between general segmentation and student segmentation, namely color attributes and the size of biodegradable tote bag products. Meanwhile, the other 4 attributes have no noticeable difference, namely texture, aroma, water resistance, and weight durability. Consumer preferences in general segmentation and the majority of students choose biodegradable tote bags that have a dark green color, smooth texture, no aroma, resistant to water, the ability to withstand a weight of > 1 kg, and measuring 30 x 40 cm.